Teknik Relaksasi Nafas Dalam Disertai Musik Religi Dapat Mengurangi Intensitas Nyeri Pada Pasien Post-Operasi Fraktur : Deep Breathing Relaxation Techniques Accompanied by Religious Music Can Reduce Pain Intensity in Post-Fracture Surgery Patients - Friska, Esra (Dohara POAJ, 2022)
Introduction: Surgery on fracture patients will cause pain, as an unpleasant emotional and sensory experience due to tissue damage. Methods: This type of research used a one-group pre-post test design. There is no comparison group (control) with a sample of 58 respondents. The standard instrument used is the Numeric Rating Scale (NRS) observation sheet. Results: From the results of univariate data testing, it was found that 77,6% of the sex distribution were male, with an age distribution of < 30 years of 58,6%. From the results of the bivariate test, it was found that there was an effect of deep breathing relaxation techniques accompanied by religious music on reducing pain intensity with a p-value of 0,000. Discussion: The result represented that there is a decrease in pain intensity after deep breathing relaxation techniques are carried out accompanied by religious music.